Materials and technologies in modern mechanical engineering : selected, peer reviewed papers from the 8th RCMME (Regional Conference on Mechanical and Manufacturing Engineering) in conjunction with the ICMME 2015 (International Conference on Mechanical and Manufacturing Engineering), November 5-6, 2015, Yogyakarta, Indonesia - Mahardika, Muslim (Applied mechanics and materials ;, 2016)
The conference theme is Green Manufacturing. The green manufacturing is a method for manufacturing that minimizes waste and pollution. Therefore, the 8th RCMME and ICMME 2015 is a place for the discussion of optimizing mechanical and manufacturing processes by minimizing waste and pollution. The aim of the conference is to facilitate the exchange of experiences and research results in all aspects of Materials and Technologies in Modern Mechanical Engineering, especially in terms of green manufacturing. Materials, Materials Processing, Applied Mechanics, Mechatronics, Control, Biomedical Engineering, Environmental Engineering, Industrial Engineering General Engineering.